1974
DOI: 10.1172/jci107646
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Acclimatization to Moderate Hypoxemia in Man

Abstract: A B S T R A C T This study has assessed the regulation of arterial blood and cerebrospinal fluid (CSF) [H+] and that the combination of chronic hypoxemia and hypocapnia of moderate degrees provided no mechanisms for the specific regulation of CSF [Hco3-] and hence for homeostasis of CSF [H+].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 37 publications
(28 reference statements)
3
49
0
Order By: Relevance
“…29 Therefore, with acute hypoxia where brain tissue pH is increased, 30 a reduced hypercapnic CVR may serve to limit brain tissue pH to rise even further. This could be promoted by diminishing the washout of hydrogen ions and facilitating the hyperventilatory response to altitude exposure by an increased ventilatory drive.…”
Section: Discussionmentioning
confidence: 99%
“…29 Therefore, with acute hypoxia where brain tissue pH is increased, 30 a reduced hypercapnic CVR may serve to limit brain tissue pH to rise even further. This could be promoted by diminishing the washout of hydrogen ions and facilitating the hyperventilatory response to altitude exposure by an increased ventilatory drive.…”
Section: Discussionmentioning
confidence: 99%
“…An arterial blood specimen was drawn over 1 min and analyzed at 37°C for pH, Paco2 and Pao2 with a Radiometer blood gas analyzer (Radiometer Co., Copenhagen, Denmark). Calibration of Pao2 and Paco2 electrodes were frequently validated using tonometered blood (17). At the same time, mixed expired gas was obtained and analyzed for C02, 02, and N2 with a gas chromatograph (QuinTron Instrument Co., Inc., Milwaukee, Wis.).…”
Section: Introductionmentioning
confidence: 99%
“…The techniques for anaerobic sampling and acid-base analyses of lumbar spinal fluid have been described previously (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our owin data obtained during acclimiatizationi points to a coimipletely different conclusion. NVe found that an increasing ventilation with time at high altitudes was not positively correlated with accoinpanying changes in CSF or plasma acidbase status or Po2 (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 89%